Hubungan Konsumsi Kopi dengan Kejadian Kecemasan pada Mahasiswa Preklinik Angkatan 2020 Fakultas Kedokteran Universitas Tadulako - Rizka Novia Idrus; Fitriah Handayani; Ketut Suarayasa; Mohammad Salman (Universitas Ahmad Dahlan, 2023)
Coffee is a beverage made from seed extract that is consumed in approximately 2.25 billion glasses per day around the world. Students are pressed for time due to the hectic lecture system and must complete assignments or prepare for block exams at night. Students can combat feelings of sleepiness and fatigue in a variety of ways, one of which is to consume caffeine-containing beverages, specifically coffee, which has the negative effect of causing anxiety disorders. The goal of this study is to see if there is a link between coffee consumption and anxiety in preclinical students from Tadulako University's Medical Faculty's batch 2020. The cross-sectional method was used in this study. Purposive sampling was used to collect the samples. The 20-item Zung Self-Rating Anxiety Scale and an 11-item coffee consumption questionnaire were used to assess anxiety. The Spearman rho correlation test was used to calculate the correlation between two variables. The criteria were met by 108 respondents, with an average age of 18.7±0.6 years, 87 women (80.6%), and 21 men (19.4%). Following coffee consumption, the level of anxiety among students was found to be dominated by the absence of anxiety or normal (73.1%), mild anxiety (24.1%), and moderate anxiety (2.8%). There was no association found between coffee consumption and student anxiety levels. This study suggested that other factors should be considered when investigating student anxiety.